1981
DOI: 10.1073/pnas.78.12.7431
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of corticotropin receptors on adrenocortical cells.

Abstract: The binding ofcorticotropin (ACTH) to receptors on isolated rat adrenocortical cells was investigated with the aid of [['25I]ITyro, Phe2, Nle4]ACTH-(1-38) (1'I-ACTH analog) which retained full biological potency and had a specific radioactivity of 1800 ± 75 Ci/mmol. Binding was highly specific to adrenocortical cells, and the radioactive peptide was displaced by low concentrations ofACTH but not by other basic peptides. Bind Despite numerous attempts to investigate corticotropin (ACTH) receptors by direct bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(51 citation statements)
references
References 31 publications
4
46
1
Order By: Relevance
“…Our results suggest that ACTH is the major regulator of these effects, since ACTH injections within 7 days restored plasma corticosterone level to control values. These results are in agreement with studies in the hypophysectomized fetal sheep, which showed that adrenal growth could be restored by in utero ACTH replacement therapy (6,8,24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that ACTH is the major regulator of these effects, since ACTH injections within 7 days restored plasma corticosterone level to control values. These results are in agreement with studies in the hypophysectomized fetal sheep, which showed that adrenal growth could be restored by in utero ACTH replacement therapy (6,8,24).…”
Section: Discussionsupporting
confidence: 92%
“…These fenestrations are the pores through which releasing factors within the hemal milieu can access the cells. In adult mammals, adrenal growth and steroidogenesis are regulated by adrenocorticotropin (ACTH) (27), which acts through interaction with a specific melanocortin receptor (MC2R) specifically expressed in the adrenal cortex (6,32). This guanine nucleotide-binding protein-coupled receptor elicits the activation of adenylate cyclase and the production of cAMP, which activate the protein kinase A-signaling pathway (39,53) and the normal functioning of adrenocortical cells.…”
mentioning
confidence: 99%
“…Before the characterization of mouse MC2R by Mountjoy et al (1992), studies in the 1970s and 1980s on the activation of the 'ACTH' receptor on mammalian adrenal cortex cells found that these cells could be stimulated by ACTH, but not by α-MSH (Schwyzer 1977). In fact, α-MSH could not competitively inhibit the binding of ACTH to the 'ACTH' receptor (Buckley & Ramachandran 1981). The critical difference between ACTH and α-MSH is the presence of the tetrabasic amino acid motif (KKRRP; Fig.…”
Section: Ligand Selectivity Of Mcrsmentioning
confidence: 99%
“…inability of a-MSH to even bind to mammalian MC2R (Buckley & Ramachandran 1981, Mountjoy et al 1992 are direct outcomes of this interaction. Studies on mammalian MRAP1 and MC2R orthologs have revealed a number of features of the MC2R/MRAP1 interaction and have raised several new questions.…”
Section: Xenopus Tropicalis Mc2rmentioning
confidence: 99%